The Metaphor of Solidarity and Hard Work in Batak Tobanese Tribe of North Sumatera - Roswita Lumban Tobing; Dwiyanto Djoko Pranowo (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
Metaphor is one cultural artifact that contains the values of a society to represent their ideas. Metaphorical expressions can be used as a basis for fostering a sense of solidarity, a spirit of cooperation, and human resource development. This exploratory research aims to explain metaphors used in ceremonial activities of Batak Toba tribe, the preservation of cultural values rooted in local linguistic treasures, revealed in the Batak Toba daily life. The data were obtained through a reading on Batak Tobanese literature about the life of the Batak society in ancient times. The validation study was conducted by in-depth interviews with experts on Batak Toba culture. The results showed that the types of methaphor used by Batak tribe is influenced by their traditional ways of life. Metaphors in Batak Toba show that the Tobanese have high solidarity. All types of metaphors in Batak Toba language motivate their communities to work hard and maintain solidarity, as well as helping other people around them. They should be maintained in the present life to gain peace, happiness, and quality of society lives.